Papel da Anandamida na modulação supraespinal da nocicepção e da antinocicepção induzida pelo estresse de derrota social - Mascarenhas, Diego Cardozo (Universidade Federal de São Carlos, 2017)
Anandamide (AEA), initially considered an endocannabinoid, has recently been described as a vanilloid agonist capable of modulating acute pain in brain regions such as the periaqueductal gray (PAG). In this context, AEA role in pain management is complex, since TRPV1 (transient receptor potential vanilloid type 1) and CB1 (cannabinoid receptors type 1) stimulation led to paradoxical effects on nociception. Moreover, acute stress, such as the social defeat, releases this compound into the PAG, making relevant its implication in the stress-induced antinociception phenomenon. Finally, the phosphorylation status of TRPV1 influences its sensitivity to AEA, which is a possible mechanism responsible for the potency and/or time length of AEA-dependent stress-induced antinociception. Herein, we have attempted to vector exogenous AEA to different receptors (i.e., TRPV1 or CB1) into mice dorsal PAG (dPAG) to reach antinociception; in addition present study aimed at elucidating the implications of local endogenous AEA in the social defeat-induced antinociception. The tail-flick test was chosen to assess acute pain. Accordingly, this CB1/TRPV1 agonist injected into mice dPAG did not change nociception. In contrast, local injections of WIN and capsaicin induced a marked CB1- and TRPV1-dependent antinociceptive effect in mice, respectively. Interestingly, only under cannabinoid blockade within mice dPAG, local AEA revealed a clear antinociceptive profile, suggesting a prominent role of this compound when it selectively binds with TRPV1. In terms of social defeat-induced antinociception, intra-dPAG blockade of either TRPV1 or CB1 attenuated the high magnitude stress-induced antinociception. Finally, intra-dPAG injections of cyclosporine A (CsA – a drug that renders TRPV1 phosphorylated, i.e., sensitive to endovanilloids) potentiated and prolonged the social defeat-induced antinociception suggesting that this mechanism of phosphorylation is pivotal to the expression of antinociception via vanilloid substrates. In conclusion, it seems that vectoring AEA to the vanilloid substrate is an interesting tool to address acute pain and perhaps translational science. Moreover, the social defeat-induced antinociception (i) seems to be subjected to a partial vanilloid/cannabinoid modulation and (ii) its magnitude and time length depend on the TRPV1 phosphorylation.
Role of Anandamide in the supraspinal modulation of nociception and social defeat-induced antinociception
Keywords: Anandamida; Substância cinzenta periaquedutal; Derrota social; Antinocicepção; Camundongos; Teste de retirada da cauda; CIENCIAS BIOLOGICAS::FARMACOLOGIA::NEUROPSICOFARMACOLOGIA